Model Vector Auto Regression (VAR) and Vector Error Correction Model (VECM) Approach for Inflation Relations Analysis, Gross Regional Domestic Product (GDP), World Tin Price, BI Rate, and Rupiah Exchange Rate - Ineu Sulistiana (Integrated Journal of Business and Economics (IJBE), 2017)
This study aims to analyze the relationship of causality of inflation, Gross Regional Domestic Product, BI rate, rupiah exchange rate to US dollar and world Tin price as one of superior commodity of Bangka Belitung Province through VAR (Vector Autoregressive) model and VECM (Vector Error Correction Model), followed by lRF (Impulse Response Function) and Variance Decomposition testing on the model to see the largest contribution of macroeconomic variables in terms of price stabilization. Based on test, estimation and model examination, VECM (1) is obtained as the best model to explain inflation causality, BI rate, rupiah exchange rate to US dollar and world Tin price, while VAR (2) is the best model to explain causal relationship of Gross Regional Domestic Product, BI rate, rupiah exchange rate to US dollar and world Tin price. The model results explain that there is a long-term causality relationship between variables, whereas the short-term causality relationship in the VECM (1) through the Granger causality test shows that the variable of granger causes inflation cause BI rate, while in VAR (2) causality between Gross Regional Domestic Product and other macro variables. Structural analysis on the VECM (1) through the analysis of variance decomposition obtained the result that the BI rate is the dominant variable contributing fluctuations in inflation, whereas, in the VAR (2), the world Tin price is the dominant variable contributing fluctuation in Gross Regional Domestic Product.